Simulação computacional de estruturas de nanodiamantes - Raota, Felipe Suliani (My University, 2019)
Nanodiamonds are studied in several application areas since their stable characteristics and remarkable physical/mechanical properties have made them an excellent material from the technological point of view. The purpose of this work is to present a solution which allows the simulation of nanodiamonds of different sizes, in a computer cluster. For that, a graphical application was developed to create and to manage the simulation’s execution. Those are carried out by the molecular dynamics method, using AIREBO (Adaptative Intermolecular Reactive Empirical Bond Order potential) and ReaxFFC−2013 (Reactive Force Field). The simulations were performed using tools developed in Python language, under the open-source software license. The main software used was ASE (Atomic Simulation Environment), LAMMPS (Large Scale Atomic/Molecular Massively Parallel Simulation) and OVITO (Open Visualization Tool). In order to facilitate the visualization of the results, scripts were developed to generate plots of temperature, total energy, potential energy and kinetic energy versus execution time. To evaluate the structural changes occurred during the simulation, resources were created that allows to visualizing the hybridizations changes during the simulation (sic).
Os nanodiamantes são objeto de estudo em diversas áreas de aplicação, uma vez que as características estáveis e propriedades físicas/mecânicas notáveis os tornaram em um excelente material do ponto de vista tecnológico. Este trabalho tem por objetivo apresentar uma solução que possibilite a simulação de nanodiamantes de diferentes tamanhos, em um cluster de computadores. Para tal, desenvolveu-se uma aplicação gráfica para criar e gerenciar a execução dessas simulações. Essas, são efetuadas por meio do método da dinâmica molecular, com uso dos potenciais interatômicos AIREBO (Adaptative Intermolecular Reactive Empirical Bond Order potential) e ReaxFFC?2013 (Reactive Force Field). As simulações foram realizadas utilizando pacotes desenvolvidos em linguagem Python sob licença de software livre, sendo que as principais ferramentas utilizadas foram ASE (Atomic Simulation Environment), LAMMPS (Large Scale Atomic/Molecular Massively Parallel Simulation) e OVITO (Open Visualization Tool). De forma a facilitar a visualização dos resultados, foram desenvolvidos scripts para geração de gráficos de temperatura, energia total, energia potencial e energia cinética em função do tempo de execução. Para avaliar as transformações ocorridas nas estruturas dos nanodiamantes ao longo das simulações, foram criados recursos que permitam visualizar as mudanças de hibridizações ao longo das simulações (sic).
Keywords: Simulação (Computadores digitais); Dinâmica molecular